2000
DOI: 10.1523/jneurosci.20-20-07838.2000
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Dopamine Transporter Function and Intracellular Accumulation of Methamphetamine: Implications for Methamphetamine-Induced Dopaminergic Neurotoxicity

Abstract: Hyperthermia exacerbates and hypothermia attenuates methamphetamine (METH)-induced dopamine (DA) neurotoxicity. The mechanisms underlying these temperature effects are unknown. Given the essential role of the DA transporter (DAT) in the expression of METH-induced DA neurotoxicity, we hypothesized that the effect of temperature on METH-induced DA neurotoxicity is mediated, at least in part, at the level of the DAT. To test this hypothesis, the effects of small, physiologically relevant temperature changes on DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 60 publications
2
76
0
1
Order By: Relevance
“…Also, as mentioned above, in situ hybridization studies indicate that although the increase in COX1 expression takes place in the substantia nigra, it occurs in the pars reticulata, in a region where GABA, rather than DA, cell bodies are located (González-Hernández and Rodríguez, 2000). Nevertheless, when we tested the effects of METH given at low ambient temperature, which induces hypothermia and prevents METH-induced DA neurotoxicity (Ali et al, 1995;Xie et al, 2000), no increase in COX1 expression was observed, further attesting to the close link between METHinduced DA neurotoxicity and increased COX1 expression. Clearly, to completely delineate the role of COX1 in METH neurotoxicity, additional studies will be necessary.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Also, as mentioned above, in situ hybridization studies indicate that although the increase in COX1 expression takes place in the substantia nigra, it occurs in the pars reticulata, in a region where GABA, rather than DA, cell bodies are located (González-Hernández and Rodríguez, 2000). Nevertheless, when we tested the effects of METH given at low ambient temperature, which induces hypothermia and prevents METH-induced DA neurotoxicity (Ali et al, 1995;Xie et al, 2000), no increase in COX1 expression was observed, further attesting to the close link between METHinduced DA neurotoxicity and increased COX1 expression. Clearly, to completely delineate the role of COX1 in METH neurotoxicity, additional studies will be necessary.…”
Section: Discussionmentioning
confidence: 85%
“…Twelve and 24 hr later, the mice were killed for Northern blot analyses of the COX1 mRNA level. Under these experimental conditions, which completely prevent METH-induced DA neurotoxicity (Xie et al, 2000), there was no increase in COX1 transcription at either 12 or 24 hr (data not shown), further suggesting that increased COX1 expression and METH-induced DA neurotoxicity are closely linked phenomena.…”
Section: Effect Of Temperaturementioning
confidence: 85%
See 1 more Smart Citation
“…Change in brain temperature is a factor that affects various neural functions ranging from the activity of ionic channels and receptor sensitivity (Thompson et al, 1985;Rosen, 2001) to such global neuronal alterations as release and uptake of neurotransmitters (Andersen and Moser, 1995;Xie et al, 2000). Thus, the METH-induced metabolic activation suggested by our temperature measurements could be a "common denominator" for various abnormalities in neural functions (i.e., thermal stress, oxidative stress, abnormal transmitter release, decrease in ATP, etc.)…”
Section: Meth Induces Pathological Metabolic Neural Activation and Hymentioning
confidence: 88%
“…One of our main goals was to prevent critical hyperthermia in naïve animals, not only as a safety issue, but also because it has been implicated as cause of METH-related neurotoxicity in acute high dose protocols (Xie et al, 2000;Riddle et al, 2002;Brown et al, 2003). One of the long-term goals of this work is to understand how METH-induced hyperther- Figure 3 Effect of METH on average total 24 h urinary cortisol excretion over the course of all three periods, Saline, METH Ramp-up, and METH Maintenance (mean7SEM).…”
Section: Discussionmentioning
confidence: 99%